Detection and localization of ice rifting and calving events in Antarctica using remote hydroacoustic stations - Gavrilov, Alexander; Vazques, G. (The Australian Acoustical Society, 2005)
Global warming induced by the greenhouse effect will affect the Antarctic ice sheet primarily in the form of disintegration of the ice shelves surrounding the continent. Calving of large icebergs can be observed post factum from satellites, whereas numerous ice shelf breaks of smaller volumes and ice rifting processes that precede the calving events are not well monitored and analysed. Detection and localization of acoustic signals emitted by ice rifting and calving in Antarctica, using remote hydroacoustic receive stations in the ocean, can be an efficient and cost-effective way to monitor disintegration of the Antarctic ice sheet. An analysis of acoustic noise recordings at the hydroacoustic listening station installed off Cape Leeuwin, Western Australia as part of the International Monitoring System of the Comprehensive Test Ban Treaty, has shown that the majority of the signals arriving from Antarctica have a pulse-like waveform, a frequency band limited within 5-30 Hz, and spectrograms that reveal strong waveguide dispersion typical for long-range propagation in the Polar environmental conditions. The azimuthal location of the detected events is not uniformly distributed along the observed sector of the Antarctica coast, and the rate of events varies with the seasons of year. The results of numerical modelling of acoustic propagation from Antarctica to the Cape Leeuwin station show that the origin of the observed signals is short, pulse-like physical processes on the Antarctic shelf, which are most likely ice rifting and calving events.